Human biology : an evolutionary and biocultural perspective - Stinson, Sara.; Bogin, Barry; O'Rourke, Dennis H. (Hoboken, NJ : Wiley-Blackwell, 2012)
"The book covers all the major areas of human biology: Genetic variation, variation related to climate, infectious and non-infectious diseases, aging, growth, nutrition, and demography. All chapters are authored by leading experts in the field. Extensively rewritten by the four authors working in close collaboration for consistent style and format, the new edition of this best-selling book also features two new chapters, one on race and culture and their ties to human biology, and the other a concluding summary chapter highlighting the integration and intersection of the topics covered in the book"--
Machine generated contents note: Introduction. Chapter 1. Human Biology: An Evolutionary and Biocultural Perspective (Sara Stinson, Barry Bogin, Dennis O'Rourke, and Rebecca Huss-Ashmore). Chapter 2. History of Human Biology in the United States of America (Francis E. Johnston and Michael A. Little). Heredity and Patterned Human Variation. Chapter 3. An Introduction to Genetics (Mark Weiss and Justin Tackney). Chapter 4. Genetics, Geography, and Human Variation (Dennis O'Rourke and Jake Enk). Chapter 5. Quantitative Variation and Genetics (Lyle Konigsberg). Human Adaptability. Chapter 6. Human Adaptation to Climate: Temperature, Ultraviolet Radiation and Altitude (Cynthia M. Beall, Nina Jablonski, and A. Theordore Steegmann, Jr.). Chapter 7. Evolution of Human Nutrition (William R. Leonard). Chapter 8. Human Energetics (J. Josh Snodgrass). Human Biology and Health. Chapter 9. The Epidemiology of Human Disease (Lisa Sattenspiel and Karen Slonim). Chapter 10. Stress and Human Biology (Gillian H. Ice and Gary D. James). The Human Life Course. Chapter 11. Evolution of the Human Life Cycle (Barry Bogin and B. Holly Smith). Chapter 12. Growth Variation: Biological and Cultural Factors (Sara Stinson). Chapter 13. Aging, Senescence and Human Variation (Douglas E. Crews and Gillian Ice). Population Dynamics. Chapter 14. Demography, Part 1: Mortality and Migration(Timothy B. Gage, Sharon N. DeWitte, and James W. Wood). Chapter 15. Demography, Part 2: Population Growth and Fertility Regulation (Peter T. Ellison, Barry Bogin, and Mary O'Rourke).
Includes bibliographical references and index.
Print version record.
Keywords: Physical anthropology; Human biology; SOCIAL SCIENCE -- Anthropology -- Physical; Human biology; Physical anthropology; Electronic books